Netrin-1 Prevents Rat Primary Cortical Neurons from Apoptosis via the DCC/ERK Pathway - Chen, Jianhao; Du, Houwei; Zhang, Yixian; Chen, Hongbin; Zheng, Mouwei; Lin, Peiqiang; Lan, Quan; Yuan, Qilin; Lai, Yongxing; Pan, Xiaodong; Chen, Ronghua; Liu, Nan (Frontiers in Cellular Neuroscience, 2017)
In the nervous system, Netrin-1 serves as a neural guide, mediating the neuronal development. However, it remains blurred whether Netrin-1 can protect neurons from apoptosis induced by cerebral stroke. In the current study, the cultured rat primary cortical neurons were transfected with Netrin-1-encoding lentivirus before the oxygen-glucose-deprivation (OGD) treatment. Cell death and apoptosis were evaluated by LDH release and flow cytometry. We found that Netrin-1 attenuated OGD-induced cell death and neuronal apoptosis at 24 hours after OGD treatment, and that the overexpression of Netrin-1 activated the ERK signaling pathway. These effects were partly abolished by blocking its receptor DCC (deleted in colorectal cancer) or U0126, an inhibitor of the ERK signaling pathway. Netrin-1 overexpression in neurons elevated the expression of DCC, on mRNA level and protein level. Netrin-1 also reduced DNA damage. Taken together, our findings suggest that Netrin-1 attenuates cell death and neuronal apoptosis via the DCC/ ERK signaling pathway in the cultured primary cortical neurons after OGD injury, which may involve the mediation of DNA damage in the neurons.